2015
DOI: 10.1111/hdi.12357
|View full text |Cite
|
Sign up to set email alerts
|

Understanding barriers to home‐based and self‐care in‐center hemodialysis

Abstract: Despite superior outcomes and lower associated costs, relatively few patients with end-stage renal disease undergo self-care or home hemodialysis. Few studies have examined patient- and physician-specific barriers to self-care and home hemodialysis in the modern era. The degree to which innovative technology might facilitate the adoption of these modalities is unknown. We surveyed 250 patients receiving in-center hemodialysis and 51 board-certified nephrologists to identify key barriers to adoption of self-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 12 publications
(12 reference statements)
2
19
0
Order By: Relevance
“…A new hemodialysis system (Tablo™ Hemodialysis System) was developed with the intention to address these issues through features such as the automation of set‐up and disconnect steps, real‐time water purification and dialysate delivery and through the use of electronic storage and transmission of treatment data. A recent survey with 50 board‐certified nephrologists suggests that the Tablo™ Hemodialysis System may expand the pool of capable patients able to perform self‐care inside and outside a clinic setting, due to the system's overall simplicity, perceived ease of use, and short training time . Patients receiving in‐center hemodialysis were also surveyed; 70% indicated that they were “likely” or “very likely” to consider self‐care if performed with the new system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new hemodialysis system (Tablo™ Hemodialysis System) was developed with the intention to address these issues through features such as the automation of set‐up and disconnect steps, real‐time water purification and dialysate delivery and through the use of electronic storage and transmission of treatment data. A recent survey with 50 board‐certified nephrologists suggests that the Tablo™ Hemodialysis System may expand the pool of capable patients able to perform self‐care inside and outside a clinic setting, due to the system's overall simplicity, perceived ease of use, and short training time . Patients receiving in‐center hemodialysis were also surveyed; 70% indicated that they were “likely” or “very likely” to consider self‐care if performed with the new system.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey with 50 board-certified nephrologists suggests that the Tablo TM Hemodialysis System may expand the pool of capable patients able to perform self-care inside and outside a clinic setting, due to the system's overall simplicity, perceived ease of use, and short training time. 15 Patients receiving in-center hemodialysis were also surveyed; 70% indicated that they were "likely" or "very likely" to consider self-care if performed with the new system.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of frequent hemodialysis are well‐documented . Yet less than 0.5% of incident ESRD patients elect home hemodialysis (in the US in 2017), where more frequent treatment is feasible, citing the need for large, complex equipment, the appointment of caretakers, and self‐cannulation as reasons to continue with the less beneficial thrice‐weekly therapies . Only a revolutionary change in therapy that improves longevity, lifestyle, and daily well‐being will disrupt the current regime of hemodialysis therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The top barriers to adoption of home-based HD include, space for equipment and supplies, lack of support/care partner, training/education limitations, self-cannulation, and medicalization of the home [20–23]. All of these hindrances can be ameliorated, to some extent, with the small form factor devices that our membranes can bring to market.…”
Section: Discussionmentioning
confidence: 99%